Space the fragile frontier - Williamson, Mark (American Institute of Aeronautics and Astronautics, 2006)
Illustrates the relevance of the space environment to science, commerce and the individual, and explains why we should consider protecting some of its properties and significant territories. This book draws together the recognized issues of Earth orbital debris and planetary protection, set them in the context of space law and ethical policies.